Suppression of the caspase-1/GSDMD-mediated pyroptotic signaling pathway through dexamethasone alleviates corneal alkali injuries. (January 2022) - Tan, Yuan; Zhang, Min; Pan, Yingzhe; Feng, Huanhuan; Xie, Lixia
Abstract: The pathological mechanism of corneal injuries mediated by alkali burns are associated with Nucleotide-binding oligomerization domain (NOD)-like receptor (NLR) family pyrin domain containing 3 protein (NLRP3)-related corneal sterile inflammation. Whether the executive protein gasdermin D (GSDMD) of pyroptosis mediated by the NLRP3 inflammasome is present in alkali-induced corneal lesions remains unclear. Dexamethasone (Dex) is a commonly used drug for ocular surface diseases that can maintain corneal transparency and anti-inflammatory effects by topical administration. Here, we presented evidence that the effect of Dex on the pyroptosis-related caspase-1/GSDMD pathway in corneal alkali burns (CABs). We assessed the clinical manifestations and histological characteristics of the placebo group, 0.05% Dex group, 0.1% Dex group on day 3 or day 7 postburn and the control group (healthy corneas). The expression of factors (including NLRP3, caspase-1, cleaved-caspase-1, GSDMD, GSDMD-N termini, pro-interleukin(IL)-1β, IL-1β, pro-IL-18 and IL-18) involved in the pyroptosis related caspase-1/GSDMD signaling pathway was demonstrated by molecular experiments in CAB. Alkali burns can upregulate the originally relatively dim expression of NLRP3, caspase-1, cleaved-caspase-1, GSDMD, GSDMD-N, pro-IL-1β, pro-IL-18, IL-1β and IL-18 in the healthy corneal epithelium and stroma. However, Dex can reverse the enhanced expression at the two timepoints. Corneal sterile inflammation can activate the NLRP3 inflammasome through the innate immune response mechanism and then activate the pyroptosis-related caspase-1/GSDMD signaling pathway. In addition, Dex can inhibit pyroptosis through this pathway. Highlights: Pyroptosis in the pathological mechanism of alkali-burned corneas is proposed. Topical application of dexamethasone can not only effectively maintain corneal transparency but also inhibit corneal neovascularization in the early-stage therapy of corneal alkali burns. Dexamethasone can suppress the pyroptosis-associated caspase-1/GSDMD signaling pathway in corneal alkali burns.